Nanoparticles of Cu–Co alloy supported on high surface area LaFeO3—preparation and catalytic performance for higher alcohol synthesis from syngas. Issue 40 (7th May 2015) - Liu, Guilong; Pan, Dongming; Niu, Ting; Cao, Ang; Yue, Yizhi; Liu, Yuan
<x xml:space="preserve">Abstract</x> Cu–Co-alloy/La2O3–LaFeO3 materials with high surface area and mesoporosity were obtained. The prepared catalysts showed excellent catalytic performance for higher alcohol synthesis.